(untitled) (Tempo e Argumento, 2021)
In this article, we look at the Constitution of a collective memory from the contribution of works consecrated as fundamental to understanding the trajectory of the theater. The works selected were: The modern theater in Pernambuco, by Joel Pontes; The theater in Pernambuco, by Alexandre Figueirôa; For a theater of the people and of the Earth, of Luís Maurício Carvalheira and TAP-your scene and your shadow, by Antonio Cadengue. With the analysis of these texts, we try to show how some theses on the theater of Pernambuco were consolidated by the regularity with which have been set out over five decades. These theses were framed in a narrative, through which different subjects and theater groups were named and challenged to prove a particular role in organizing memory consists of this narrative, under pain of falling into Oblivion for lack of relevance. In this sense, the constitution of a collective memory, as we have studied here, does not have as its main theme a correspondence between the discourses analyzed and the "real", but the internal coherence of a consecrated narrative and its ideas about the Pernambuco theater. Keywords: history; memory; theatre of Pernambuco; genealogy.